Faktor-Faktor Yang Mempengaruhi Kepuasan Pengunjung: Studi Kasus Pada Wisata Pemandian Air Panas Bukit Kili, Kabupaten Solok - Esi Sriyanti; Arfimasri Arfimasri; Mesi Afrita (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to Factors that Influence Visitor Satisfaction: Case Study of Bukit Kili Hot Springs Tourism, Solok Regency with a sample of 100 respondents who were studied using quantitative methods. Based on the results of statistical analysis, it can be interpreted that Service Quality partially has a significant effect on Visitor Satisfaction, this is proven by the t test with a significant value of tcount 24,043 > ttable 1.66071 and a significance value of 0.000 < 0.05. So it can be interpreted that the development of Service Quality has a significant effect on Visitor Satisfaction. Based on the results of statistical analysis, it can be concluded that infrastructure partially has a significant effect on visitor satisfaction at the Bukit Kili Hot Springs Tourism, Solok Regency. This is proven by the t test with a significant value of tcount 22,572 > ttable 1.66071, and a significance value of 0.005 < 0.05. So it can be concluded that Infrastructure has a significant effect on Visitor Satisfaction. Simultaneously, the quality of service and infrastructure has a significant effect on visitor satisfaction at the Bukit Kili Hot Springs Tourism, Solok Regency. This is proven by using the F test with a significant value of fcount 304.933 > ftable 3.09 with the resulting significance of 0.000, this value is much smaller than (0.05). This can also be seen from the R Square value obtained at 0.863 or 86.3% and the remaining 13.7% is influenced by other variables not included in this research.